Level of anxiety and fear of COVID-19 in adolescents during the post-pandemic in the city of Juliaca and Tacna, 2022 - Mamani Quispe, Yeny (2023)
Objective: to measure the levels of anxiety and fear of COVID 19 in adolescents in the city of Juliaca and Tacna during the post-pandemic period. Methodology: non-experimental design, presents characteristics type of a descriptive-comparative research, cross-sectional and quantitative approach, non-probabilistic sampling. It was possible to survey 250 adolescents both, sexes from 13 and 17 years old. Results: in the study, it was observed that 39.2% showed a minimum level of anxiety, 38.4% a slight level, 15.6% a moderate level and finally 6.8% showed a severe level of anxiety. Regarding the other variable, 43.2% presented a very low level of Fear of COVID 19, 49.6% medium level and 7.2% the high level. Conclusion: According to the results, it is possible to visualize that adolescents presented a positive percentage in both variables of 39.2% and 43.2%. Demonstrating that a high percentage of adolescents no longer present anxiety and fear of COVID 19. Although we still observe a minimum percentage in both variables of 6.8% and 7.2%, these results demonstrate the importance of continuing to raise awareness by MINSA as well tan educational institutions.